Inflation and Stabilization in Transition Economies : A Comparison with Market Economies - Vegh Gramont, Carlos (IMF Working Papers; Working Paper ;, 1995)
A simple model is developed to understand inflationary pressures and stabilization in nonmarket economies. In light of the model, the paper reviews the inflation and stabilization experiences of several transition economies in Eastern Europe and the former Soviet Union. These experiences are then compared to those of high inflation market economies. The paper concludes that, despite significant differences in the economic structure and institutional framework, the inflation and stabilization experiences in transition and market economies are similar in many respects. In particular, monetary accommodation and lack of fiscal discipline are critical in sustaining inflation, and exchange rate-based anchors seem more successful than money anchors in bringing down inflation. On the other hand, wage policies appear to be more critical in reigning inflation in transition economies than in market economies.